Differential effects of a reading strategy intervention program for migrant children in migrant schools in China - Guo, Qian; Kim, Young-Suk; Liu, Yan; Peng, Yan; Sun, Wenkai; Yan, Jin; Yang, Li (Frontiers in Education, 2023)
Background There are over 14 million migrant children in the compulsory education system in China and the number has been increasing rapidly. However, the quality of education in schools for migrant children is often poor. Meanwhile, numerous studies indicated the importance of reading skills developed by the end of third grade. Few studies, however, have investigated the early reading development of migrant children in migrant schools in China. In the current study, we examined, with a randomized control trial design, the effects of reading strategy instruction via teacher professional development for migrant children in migrant schools. Method A total of 1,679 students from 47 third-grade classes in 13 migrant schools for migrant children in Beijing, China, participated in the study. The intervention was composed of teacher professional development on reading strategy. Students in both treatment and control conditions received books for independent reading. Results The program resulted in a higher overall reading performance for students in the treatment classes than those in the control classes, with the difference larger in inferential comprehension and for students who did not live in Beijing before starting elementary school (which we speculate captures the degree of family mobility and the rural–urban gap in the access to educational resources). Conclusion The results suggest that a reading strategy instruction via teacher professional development may promote the reading development of migrant children in migrant schools in China.